Concordance between Gleason score of prostate biopsies and radical prostatectomy specimens and its predictive factors. Issue 2 (May 2023) - Ariafar, Ali; Rezaeian, Ali; Zare, Ali; Zeighami, Shahryar; Hosseini, Seyed Hossein; Nikbakht, Hossein-Ali; Narouie, Behzad
Objective: The Gleason score is an essential factor for making decisions about prostate cancer management and its prognosis. Thus, we conducted this research to discover the histologic-grading accuracy of needle biopsy specimens, and to identify preoperative clinical and pathological factors that predict upgrading and downgrading from biopsy to radical prostatectomy specimen. Patients and methods: This study was performed on 570 patients who were referred to the medical centers affiliated with Shiraz University of Medical Sciences and underwent radical prostatectomy from 2013 to 2017. Concordance was evaluated between the Gleason score of needle biopsy and radical prostatectomy specimens. Predictors of upgrades and downgrades were assessed in univariate and multivariate logistic regression analyses. Results: Scores were the same in 50% of cases, downgraded in 26%, and upgraded in 24%. The variables predicting a Gleason score upgrade were higher Prostate specific antigen level, larger tumors, and older age. Lower tumor volume, lower Prostate specific antigen, and low maximum percentage of cancer in cores were predictors of downgrading from Gleason score>6 to ⩽6. Also, Body mass index>30, smaller tumor size, and negative lymph nodes were predictors of downgrading from Gleason score>7 to 7. Conclusion: The correlation between biopsy and Radical prostatectomy Gleason scores was only 50%. After dividing them into the new grading groups, this coordination increased by only 5.6%. Physicians need to consider possible limitations of the Gleason score of biopsy and factors that can be predictive of upgrading to high-risk prostate cancer before making treatment decisions.